SOME ISSUES OF DAGESTAN’S INTEGRATION INTO THE POLITICAL SYSTEM OF THE RUSSIAN EMPIRE AND POLITICAL CULTURE OF DAGESTANIS - Muslimova, Naida Tagirova (History, Archeology and Ethnography of the Caucasus, 2022)
The paper is based on modern approaches of historiography, sociology, political science, documentary sources: archive materials, periodicals, memoirs. Applying the principles of historicism, methods of comparative-historical, comparative-legal analysis, we have examined the political culture of the Dagestan peoples, united after the Caucasian War within the administrative-territorial borders of the Dagestanskaya Oblast of the Russian Empire (1860-1921). The paper aims to assess the basic norms and values, beliefs, political orientations, and standards of political behavior of the Dagestan peoples as subjects of the common political, economic and cultural process; to trace how the preservation of traditional historical legal provisions (Adat and Sharia law) and rural community as a main structural element of the Dagestan society contributed to the viability and stability of the new political system and, at the same time, how the dynamics of the socio-economic and cultural development of the new socio-political community and the processes of adaptation of socio-cultural traditions associated with it to the socio-historical reality were reflected in the political culture of the Dagestanis. The study demonstrates that despite the change in the forms of interaction between power and society, the emergence and functioning of new socio-political institutions and concepts of the socio-political structure, by the time of the October Revolution and the Civil War (1918-1921), the political culture of the majority of Dagestanis in its main values and patterns of political behavior has retained its traditional features and orientations – belonging to a rural community and Adat and Sharia as norms for regulating public life.
Keywords: the political culture of the Dagestanis; ethical distance; zemstvo reform in Dagestan; adat; sharia; Dagestan region